Factors Associated with Anemia Among Children 6–23 Months of Age in Ethiopia: A Multilevel Analysis of Data from the 2016 Ethiopia Demographic and Health Survey - Gebrehaweria Gebremeskel M; Lemma Tirore L (Dove Medical Press, 2020)
Menaseb Gebrehaweria Gebremeskel,1 Lire Lemma Tirore2 1Department of Public Health, College of Medicine and Health Sciences, Adigrat University, Adigrat, Tigray Ethiopia; 2Department of Public Health, College of Medicine and Health Sciences, Wachemo University, Hossana, Southern Nations Nationalities and peoples, EthiopiaCorrespondence: Menaseb Gebrehaweria GebremeskelDepartment of Public Health, College of Medicine and Health Sciences, Adigrat University, PO Box: 50, Adigrat, Tigray, EthiopiaTel +251 3 48870000Fax +251909850754Email menasebgh@gmail.comBackground: Anemia is disproportionately borne among children in the African regions including Ethiopia. In Ethiopia, there is limited information on the prevalence and factors associated with anemia among children aged 6– 23 months. Therefore, the aim of this study was to identify individual- and community-level factors associated with anemia among children 6– 23 months of age.Methods: The data were obtained from the 2016 Ethiopia Demographic and Health Survey, conducted from January to June 2016. A sample of 2554 children aged 6– 23 months was included. Data were analyzed using STATA version 14. A multilevel ordinal logistic regression model was fitted and an adjusted odds ratio with a 95% confidence interval was obtained.Results: The prevalence of anemia among children 6– 23 months of age was 72.3%; 27.5% mild, 41% moderate, and 3.8% severe anemia. child age 18– 23 months (AOR: 0.76; 95%CI: 0.61– 0.93), female sex (AOR: 0.84; 95%CI: 0.72– 0.98), maternal anemia (AOR: 1.53; 95%CI: 1.28– 1.82), exclusive breastfeeding (AOR: 0.73; 95%CI: 0.54– 0.98), child fever (AOR: 1.41; 95%CI: 1.03– 1.93), underweight children (AOR: 1.42; 95%CI: 1.17– 1.73) and exposure to either newspaper, radio or television (AOR: 0.78; 95%CI: 0.61– 0.99) were the individual-level factors associated with anemia. High community-poverty (AOR: 1.30; 95%CI: 1.01– 1.67), living in the regions of Somali (AOR: 2.08; 95%CI: 1.31– 3.29), Amhara (AOR: 0.65; 95%CI: 0.45– 0.94), Benishangul (AOR: 0.39; 95%CI: 0.25– 0.61) and Harari (AOR: 1.97; 95%CI: 1.18– 3.31) were the community-level factors associated with anemia.Conclusion: This study showed that childhood anemia is affected both by the individual- and community-level factors. The strategies of promoting exclusive breastfeeding, addressing maternal anemia, child fever, giving special attention for underweight children, and targeting regions identified to have a high risk of anemia should be strengthened to reduce childhood anemia.Keywords: anemia, individual- and community-level factors, feeding practices, ordinal logistic regression